(untitled) (Journal of Computational Mathematics, 2003)
In this paper we introduce a primal-dual potential reduction algorithm for positive semi-definite programming. Using the symetric preserving scalings for both primal and dual interior matrices, we can construct an algorithm which is very similar to the primal-dual potential reduction algorithm of Huang and Kortanek [6] for linear programming. The complexity of the algorithm is either O(n (X^0· S^0/ε)) or O(n(X^0· S^0/ε)) depends on the value of ρ in the primal-dual potential function, where X^0 and S^0 is the initial interior matrices of the positive semi-definite programming.